Imaging of the Entry Pathway of a Cell-Penetrating Peptide–DNA Complex From the Extracellular Space to Chloroplast Nucleoids Across Multiple Membranes in Arabidopsis Leaves - Oikawa, Kazusato; Tateishi, Ayaka; Odahara, Masaki; Kodama, Yutaka; Numata, Keiji (Frontiers in Plant Science, 2021)
Each plant cell has hundreds of copies of the chloroplast genome and chloroplast transgenes do not undergo silencing. Therefore, chloroplast transformation has many powerful potential agricultural and industrial applications. We previously succeeded in integrating exogenous genes into the chloroplast genome using peptide–DNA particles composed of plasmid DNA and a fusion peptide consisting of a cell-penetrating peptide and a chloroplast transit peptide (cpPD complex). However, how cpPD particles are transported into the chloroplast from outside the cell remains unclear. Here, to characterize the route by which these cpPD particles move into chloroplasts, we tracked their movement from the extracellular space to the chloroplast stroma using a fluorescent label and confocal laser scanning microscopy. Upon infiltration of cpPD particles into the extracellular space of Arabidopsis thaliana leaves, the particles reached the chloroplast surface within 6 h. Next, they were engulfed by the chloroplast outer envelope membrane and gradually integrated into the chloroplast. We detected several cpPD particles localized around chloroplast nucleoids and observed the release of DNA from the cpPD. Our results thus define the route taken by the cpPD particles for gene delivery from the extracellular space to the chloroplast stroma.